BATAS USIA PERKAWINAN DI INDONESIA DAN BRUNEI DARUSSALAM PRESPEKTIF IMAM MAZHAB - ilham ilham (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
The age limit for marriage is one of the things that determines the maturity or marriage maturity, so that those who want to get married can distinguish between good and bad. Renewal of Islamic law in Indonesia in terms of the age limit for marriage which was previously stated in article 7 of law no. 1 of 1974 concerning marriage stipulates that the maximum age of marriage for men is 19 years and 16 years for women. After the reform of the law, the maximum age for marriage is 19 years for both men and women. In addition, in the country of Brunei Darussalam there are 3 regulations that discuss the age limit for marriage, including the Chinese marriage law explaining the age limit for marriage, which is 15 years, the Christian marriage law explaining the marriage age limit is 14 years for men and women, and the law Islamic family law stipulates that the age limit for marriage is 18 years for men and 16 years for women. The age limit for marriage according to the scholars of the school of thought has several differences of opinion. Scholars of the Shafi'i and Hanbali schools are of the opinion that the ideal age of puberty in marriage is 15 years, while Abu Hanifah believes that the age of maturity comes at the age of 18 for men and 17 years for women, while Imam Malik believes that the limit for marriage is 17 or 18 years. Keywords: Age limit, Indonesia and Brunei Darussalam, Ulama Mazhab